SOSIALISASI DAN EDUKASI KONSEP BANK SAMPAH SERTA EKONOMI SIRKULAR KEPADA MASYARAKAT DI KELURAHAN GALANG BARU, KECAMATAN GALANG, KOTA BATAM - Piariska, Suci; Rahmadani, Wulan; Ramanda, Melda; Neva, Ivena; Rivana, Farrah Pradwita; Aramadaniyas; Putri, Alifia Sulistyani Aryana; Anjani, Analinda Putri; Richmayati, Maya (Jurnal Pengabdian Ibnu Sina, 2026)
Waste management has become an increasingly serious environmental issue along with population growth and the intensification of community activities, particularly in developing areas. Low public awareness of sustainable waste management often leads to waste accumulation, which negatively affects environmental quality, public health, and local ecosystem balance. This community service program aimed to improve community understanding and active participation in waste management through the implementation of the waste bank concept and circular economy principles. The activity was conducted in Galang Baru Village, Galang District, Batam City, using a participatory approach that actively involved community members. The program included socialization on the environmental and health impacts of waste, interactive education on the economic value of waste, and technical training on proper sorting of organic and inorganic waste. The results showed a significant improvement in participants’ knowledge of waste bank operations and the potential of waste as an alternative economic resource. As a tangible outcome, the community successfully initiated the establishment of an independent waste bank and began applying household recycling practices. Although challenges remain, such as changing long-standing habits and limited supporting infrastructure, strong community enthusiasm serves as important social capital. The sustainability of this program is expected to support community economic independence while promoting long-term environmental conservation.